Survey Keterampilan Gerak Dasar Non Lokomotor Pada Siswa Kelas 1 SD Negeri 161 Pekanbaru - Helmalia Putri; Aras Vaghira; Rehan Randesto; Yeni Yeni (Jurnal Inovasi Olahraga, 2026)
The aim of this research is to assess the proficiency of non-locomotor basic movement skills among students of class 1 at SDN 161 Pekanbaru. The research conducted is a quantitative descriptive study, employing survey methods and data collection techniques involving tests and observations. The research indicates that the proficiency of non-locomotor basic movement skills falls into several categories: Very Low: 2 students, accounting for 7.14%,  Low to Above Average: 4 students, comprising 14.28%, Below Average: 6 students, representing 21.24%, Many students still fall into the average category, with 12 students, or 42.85%. These findings serve as a basis for developing non-locomotor basic movement skills among first-grade students at SDN 161 Pekanbaru, as well as data for evaluating the programs that have been implemented. Thus, this research holds significant relevance in enhancing the understanding and development of non-locomotor basic movement skills at the elementary school level.